Electrostatic probe analysis of SiO2 activating flux powders transition behavior in Powder Pool Coupled Activating TIG alternating current arc plasma for aluminum alloy. (December 2022) - Huang, Yong; Li, Qianpeng; Xue, Xupu; Xu, Hang; Huang, Jiankang; Fan, Ding
Abstract: In alternating current Powder Pool Coupled Activating TIG welding for aluminum alloy, activating flux powders are transferred into the arc-pool coupling system through the outer gas to dramatically improve the weld penetration. The transition behavior of activating flux powders affects the weld penetration and forming intensely. To clarify the transition process of powder particles of activating flux SiO2 in the arc and its influence law and mechanism on arc characteristics, electrostatic probe powder capturing technology was developed to in-situ capture the in-flight powder particles at the expected position. Then, combined with SEM/EDS and thermodynamic calculation of the captured particles and spectrum diagnose of plasma compositions, the physicochemical process of SiO2 activating flux powder particles in the arc plasma was determined. Meanwhile, the influences of activating powders on current-carrying region, temperature and voltage of arc plasma were examined. The results show that, in the increase with heating time, the physical processes such as heating, melting, evaporation, breakage, collision, and fusion of SiO2 activating powders in the arc occur successively. The dissociation of SiO2 promotes the ionization of Ar and Al elements in the arc plasma. Compared with traditional TIG welding, the transition of activating flux powders makes the arc constrict, at the same time, the temperature along the axial centerline of arc raises, and the arc voltage significantly increases, all of which contributes to the obvious increase in weld penetration through SiO2 activating flux.